2013
DOI: 10.1016/j.leukres.2013.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Myelodysplastic syndromes and autoimmune diseases—Case series and review of literature

Abstract: Our objective was to recognize the association of autoimmune disease (AD) in patients with myelodysplastic syndromes (MDS) and understand how this association could affect prognosis and management of both diseases. We describe our cohort of 10 patients and 34 patients reported in the English literature in addition to ten cohort studies. Interestingly, four cases showed improvement in AD after 5-azacitidine treatment. The mechanism(s) of the association between AD and MDS are discussed. Treatment could be targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 53 publications
1
50
0
2
Order By: Relevance
“…A Swedish population-based study demonstrated a strong association between chronic immune stimulation and MDS predisposition, where a history of autoimmune disease was associated with a two-fold significantly increased risk of MDS (OR 2.1 [95% CI 1.7-2.6]) [6]. Small case series have reported distinct clinical features and outcomes for MDS patients with autoimmune diseases [7]. We report here, in a large cohort, the prevalence of autoimmune diseases among MDS patients and compare characteristics and outcomes of MDS patients with and without autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%
“…A Swedish population-based study demonstrated a strong association between chronic immune stimulation and MDS predisposition, where a history of autoimmune disease was associated with a two-fold significantly increased risk of MDS (OR 2.1 [95% CI 1.7-2.6]) [6]. Small case series have reported distinct clinical features and outcomes for MDS patients with autoimmune diseases [7]. We report here, in a large cohort, the prevalence of autoimmune diseases among MDS patients and compare characteristics and outcomes of MDS patients with and without autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Association with inflammatory myopathies has been very rarely described (8)(9)(10)(11)(12)(13)(14)(15). In particular, in the case report published by Tsuji et al, antinuclear antigens were found, but the assay for anti-Jo1, RNP and Scl70 resulted negative.…”
Section: Case Reportmentioning
confidence: 99%
“…Collectively, the incidence of this association has been reported in several retrospective analyses to be in the range of 7-25% of MDS patients [10]. However, these studies differ in their definition of MDS and vary in their definition for MDS-associated AICs (table 1).…”
Section: The Spectrum Of Systemic Aics In Mdsmentioning
confidence: 99%
“…One systematic review summarized data from 10 retrospective studies dating from the early 1990s to 2009 and found vasculitides (isolated or systemic) to be the most frequent diagnosis in patients with MDS and an associated AIC (40%), followed by seronegative arthritis (27%), neurologic disease (24%), bronchiolitis obliterans with organizing pneumonia/interstitial pulmonary fibrosis (15%), glomerulonephritis (12%), rheumatoid arthritis (12%), and Sweet's syndrome (10%) [10]. …”
Section: The Spectrum Of Systemic Aics In Mdsmentioning
confidence: 99%